Spontaneous and CRH-Induced Excitability and Calcium Signaling in Mice Corticotrophs Involves Sodium, Calcium, and Cation-Conducting Channels - Zemkova, Hana; Tomić, Melanija; Kucka, Marek; Aguilera, Greti; Stojilkovic, Stanko S (Endocrinology, 2016)
Transgenic mice expressing the tdimer2(12) form of Discosoma red fluorescent protein under control of the proopiomelanocortin gene's regulatory elements are a useful model for studying corticotrophs. Using these mice, we studied the ion channels and mechanisms controlling corticotroph excitability. Corticotrophs were either quiescent or electrically active, with a 22-mV difference in the resting membrane potential (RMP) between the 2 groups. In quiescent cells, CRH depolarized the membrane, leading to initial single spiking and sustained bursting; in active cells, CRH further facilitated or inhibited electrical activity and calcium spiking, depending on the initial activity pattern and CRH concentration. The stimulatory but not inhibitory action of CRH on electrical activity was mimicked by cAMP independently of the presence or absence of arachidonic acid. Removal of bath sodium silenced spiking and hyperpolarized the majority of cells; in contrast, the removal of bath calcium did not affect RMP but reduced CRH-induced depolarization, which abolished bursting electrical activity and decreased the spiking frequency but not the amplitude of single spikes. Corticotrophs with inhibited voltage-gated sodium channels fired calcium-dependent action potentials, whereas cells with inhibited L-type calcium channels fired sodium-dependent spikes; blockade of both channels abolished spiking without affecting the RMP. These results indicate that the background voltage-insensitive sodium conductance influences RMP, the CRH-depolarization current is driven by a cationic conductance, and the interplay between voltage-gated sodium and calcium channels plays a critical role in determining the status and pattern of electrical activity and calcium signaling.
Keywords: dibutyryl cyklický AMP; kultivované buňky; kolforsin; membránové potenciály; metoda terčíkového zámku; Calcium Channels, L-Type; akční potenciály; iontové kanály; Corticotropin-Releasing Hormone; AMP cyklický; myši transgenní; Action Potentials; Arachidonic Acid; vápník; myši inbrední C57BL; Calcium Signaling; mužské pohlaví; Mice, Inbred C57BL; Corticotrophs; Patch-Clamp Techniques; vápníkové kanály - typ L; Membrane Potentials; Cyclic AMP; Calcium; Cells, Cultured; Animals; ženské pohlaví; vápníková signalizace; zvířata; sodík; kyselina arachidonová; kortikotropní buňky; Ion Channels; Bucladesine; Female; Sodium; Mice, Transgenic; Colforsin; Male; hormon uvolňující kortikotropin